The Evolution of Fermented Milks, from Artisanal to Industrial Products: A Critical Review - Bintsis, Thomas; Papademas, Photis (My University, 2022)
The manufacture of fermented milk products has a long history, and these products were initially produced either from spontaneous fermentation or using a batch of previously produced product, that is, back-slopping. Milk of different mammal species has traditionally been used for the manufacture of fermented milk products. Cow’s milk is the basis for most dairy fermented products around the world. Milk from other mammals, including sheep, goat, camel, mare, buffalo, and yak may have been historically more important and remain so in certain regions. The milks from different species have differences in chemical composition and in certain, vital for the fermentation, components. The diversity of fermented milk products is further influenced by the wide variety of manufacturing practices. A great number of fermented dairy products have been traditionally produced worldwide, and many of them are still produced either following the same traditional process or manufactured industrially, using standardized processes under controlled conditions with specified starter cultures. The evolution from traditional to industrial production, their specific regional differences, their special characteristics, and the microbiological aspects of fermented dairy products are discussed. Throughout the evolution of fermented milk products, functional and therapeutic properties have been attributed to certain components and thus, yogurts and fermented milks have gained a significant market share. These products have gained wide global recognition as they meet consumers’ expectations for health-promoting and functional foods. The exploitation of microbiological methods based on DNA (or RNA) extraction and recently high-throughput techniques allowed for the accurate identification of the microbiota of fermented milk products. These techniques have revealed the significance of the properties of the autochthonous microbes and provided novel insights into the role of the microbiota in the functional and organoleptic properties of many fermented milk products.
Keywords: back-slopping; fermented dairy products; fermented milk products; kefir; spontaneous fermentation; yogurt